THE METHOD FOR FAST DETERMINATION OF GEOSTATIONARY ARTH SATELLITE ORBIT FROM ANGULAR COORDINATES MEASUREMENTS - Bazyey, O. A.; Sibiryakova, E. S.; Shulga, A. V. (Одеські астрономічні публікації, 2017)
Classical Laplas method for determination of Keplerian orbital elements is described. The values obtained are improved by the method of differential corrections. The software has been provided and realizes such an algorithm to calculate orbital elements for high artificial Earth satellites. The approach suggested is used in processing artificial Earth satellites observations at Nikolayev Astronomical Observatory (NAO). Examples are given of orbit calculations for some geostationary satellites.